Narrative in the Age of the Genome Genetic Worlds - Choksey, Lara (Explorations in Science and Literature, 2021)
Shortlisted for the 2021 BSLS Book Prize Genomic technologies have had a profound impact on understandings of what it means to be human and our links to the world we inhabit, and on practices of inhabiting the world. This open access book considers this impact across a range of literary forms, cultural practices, and political imaginaries, and argues that new descriptions of biological value introduced through practices of genomic sequencing from the late 1970s registered a broader crisis of narrative form. Examining a wide range of texts by Doris Lessing, Samuel Delany, Boris and Arkady Strugatsky, Kir Bulychev, Kazuo Ishiguro, Saidiya Hartman, Yaa Gyasi, Svetlana Alexievich, and Jeff VanderMeer, Narrative in the Age of the Genome casts new light on the intersections of genomics with politics of racism, sexuality, labour and gender, neoliberal economics and environmental crisis. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The Wellcome Trust